Konsumpcja i prosumpcja w rodzinach województwa kujawsko-pomorskiego - Nowak, Waldemar (Wydawnictwo Naukowe UAM, 2002)
The article is the presentation of the results of the research conducted in 1999-2001, in Kujawy and Pomerania Region. The research covered 200 families and their domestic arrangements, varying according to the pace of living, financial income, education, ways of earning the living, age and structure. There were the following methods used: questionnaires, observations, documents analysis and free interview.
Consumption and prosumption in housekeeping in Kujawy and Pomerania Region